MAQASID AL-SYARIAH AS A NORMATIVE FRAMEWORK FOR ISLAMIC MICROECONOMICS: ANALYSIS OF MICRO WAQF BANKS IN INDONESIA - Muhamad Zainal Abidin; Fachrudin Fiqri Affandy (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze Micro Waqf Banks (BWM) as an Islamic microeconomic practice using Maqasid al-Syariah as a normative evaluative framework, focusing on wealth protection (ḥifẓ al-māl) and life protection (ḥifẓ al-nafs), and to examine whether these maqāṣid orientations have been explicitly institutionalized. The study employs a qualitative normative-conceptual approach with a library‑based research design. Data were drawn from waqf regulations, official BWM documents, Islamic financial institution publications, and relevant academic literature. Results indicate that BWM functions as an Islamic microeconomic institution that structurally integrates philanthropic values with Sharia financing mechanisms. BWM practices demonstrate strong alignment with ḥifẓ al-māl through productive waqf fund management and collateral‑free financing, and with ḥifẓ al-nafs through inclusive financial access and holistic mentoring programs. However, this maqāṣid orientation remains implicit and has not been institutionalized through formal indicators, evaluation standards, or governance mechanisms. The study advances five original theoretical contributions: (1) maqasid‑embedded institutional design; (2) the maqasid multiplier mechanism, whereby a single program generates cascading outcomes across multiple maqasid dimensions; (3) nascent maqasid institutionalization as a distinct intermediate governance phase; (4) the institutionalization gap as a generalizable diagnostic concept for Islamic microfinance; and (5) maqasid accountability as an irreducible dimension of institutional legitimacy for Islamic social finance. The findings provide a normative governance roadmap for BWM management and offer policy recommendations for regulators seeking to develop maqasid‑based evaluation standards for Islamic microeconomic institutions in Indonesia. This study is limited to normative‑conceptual analysis based on secondary data without field observation, focusing only on two Maqasid dimensions. Future research should conduct empirical studies and field observations, and incorporate additional maqasid dimensions to validate and extend the proposed framework. This study offers novelty by positioning Maqasid al‑Syariah as an operational normative framework for evaluating Islamic microfinance institutions, providing insights for developing comprehensive evaluation instruments, and informing policy formulation by integrating maqāṣid values into Islamic microeconomic governance.